ADVOCATE IMMUNITY: QUO VADIS OF VALUE AND ETHICS IN LEGAL NORMS? - Rocky Marbun (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2019)
If the value in the ethics of a particular profession is attributed to the property of that particular profession, then the judgment of a 'good faith' offense can only be traced through a mutual consensus agreed upon by those in the profession. However, in this case, the Researcher is not in a position to say an Advocate can not be convicted. The researcher is more respectful of the value that should be heard and raised surface on the hegemony of legal norms.